Clinical profile of dengue fever in children in a university level medical college of North India - Sharma, Raman; Khajuria, Kajal (International Journal of Advances in Medicine, 2022)
Background: Dengue epidemics are more frequent in developing countries like India. Dengue is a self-limiting disease but its complication in children may cause high morbidity and mortality. Objective: The main objective of this study was to assess the clinical profile of dengue fever in children less than 15 years of age. Methods: This was a retrospective study done in a pediatric department of Maharishi Markandeshwar institute of medical science and research hospital, Ambala, a university level medical college of North India for a period of 17 months. Results: A total of 130 patients of dengue fever were identified in our study. Out of these 130 patients, 39 patients were included in dengue without warning signs,78 were included in dengue with warning signs and 13 in severe dengue category. The most common age group was between 5 to 10 years of age. Fever was the most common presenting symptom in all dengue patients. No mortality was observed during our study period due to dengue. Conclusions: It is one of the dreaded fevers for all the pediatric age group. So, early suspicion and effective management can reduce the severity.